2020
DOI: 10.21608/adjc.2020.21032.1043
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Marginal Gap Distance of CAD/CAM Milled BioHPP PEEK Coping Veneered by HIPC Compared to Zirconia Coping Veneered by CAD-On lithium disilicate “In-Vitro Study”

Abstract: Statement of problem: marginal inaccuracy causes a space between restoration and prepared tooth, which accelerates cement dissolution, leading to secondary caries, pulpal lesions, postoperative sensitivity, periodontal disease and marginal discoloration. Marginal gap should be less than 120µm. Aim: to evaluate vertical marginal gap of PEEK (Bio-HPP) veneered with CAD/CAM composite veneer (HIPC) as compared to zirconia veneered with CAD-On lithium disilicate glass ceramic. And the effect of ageing on the gap of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…Veneering of BioHPP PEEK copings started with application of dual-hardening combo.lign opaque as a first layer (wash opaquer) followed by crea.lign opaque on the BioHPP coping. They were polymerized for 180 seconds [14].…”
Section: Visitmentioning
confidence: 99%
See 1 more Smart Citation
“…Veneering of BioHPP PEEK copings started with application of dual-hardening combo.lign opaque as a first layer (wash opaquer) followed by crea.lign opaque on the BioHPP coping. They were polymerized for 180 seconds [14].…”
Section: Visitmentioning
confidence: 99%
“…lign polishing Kit. They ensure a perfect finish and surfaces with high plaque resistance and shade stability [14] (Figure 3a).…”
Section: Visitmentioning
confidence: 99%
“…132420) before pressing them on the cores utilizing a device delivering a uniform load of 5 kg (49 N) for 10 minutes. 12 Then, 180 seconds polymerization was performed at 220 mW/cm 2 (brelux Power Unit; bredent Senden, Germany). Each crown was then polished (Opal L, Renfert GmbH, Hilzingen, Germany; Lot No.…”
Section: Preparation Of Specimensmentioning
confidence: 99%
“…The values are less than those observed by Shin et al, Who reported internal discrepancies for CAD-CAM endocrowns of 200–300 μm [ 43 ]. This difference could be attributed to the fact that the internal fit of endocrowns is influenced by the cavity depth, restoration material and processing techniques [ 44 ].…”
Section: Discussionmentioning
confidence: 99%